Mechanized Cultivation Increases Labour Efficiency (Bangladesh Rice Journal, 2021)
Farm mechanization facilitates to increase agricultural productivity and improves farm management by replacing human labour. Therefore, mechanical intervention is a vital adaptation strategy for a sustainable rice production system. Thus, this study aims to (i) estimate the amount of mechanical in-tervention required in rice cultivation, particularly in transplanting and harvesting operation; and (ii) delineate the impact of farm mechanization on rice productivity and employment generation. The primary data were collected through a household survey and key informant interviews. These data were used for projecting rice area, labour requirement, and off-farm employment opportunities in rice cultivation. Besides, secondary data were collected from published literature. The break-even la-bour requirement per hectare rice cultivation was 2.88 work-days. Labour productivity might be doubled by 2030 subject to bringing 42% and 36% of the total rice area under mechanical transplant-ing and harvesting, respectively. The projected demands of the transplanter and combine harvester to achieve the goal are 49,172 and 28,382, respectively. The mechanized rice transplanting, weeding, and harvesting reduced labour requirement by 29, 26, and 34%, respectively, compared to the manual op-erations. Besides, mechanization meets up the demand for labour at a seasonal peak and increases rice productivity. Furthermore, it creates some off-farm (e.g., operating) and non-farm (e.g., manufac-turing, repairing, and trading) employment opportunities for operating, maintenance, fabricating, and marketing of the machinery. Syncronize farming is required for enhancing the field efficiency of the farm machine at present size and shape of plots. Besides, the synchronized farming is beneficial for providing service to the farmers at their affordable rental charge. Government assistance should continue and strengthen for the procurement of transplanters and combine harvesters. A holistic ap-proach combining the public and private intervention is essential for achieving the mechanized farm-ing goal for sustainable rice farming in Bangladesh.Bangladesh Rice J. 24 (2): 49-66, 2021